A note on an inequality for the gamma function - Christopher Olutunde Imoru (International Journal of Mathematics and Mathematical Sciences)
Some inequalities for the Wallis functions are proved. The results of this paper are consequences of some characterization of convex functions. A generalization of a result of Boyd (1) and an extentlon of an inequality of Gantschi (3) are obtained.